2007
DOI: 10.1117/12.752830
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the understanding of fracture related laser damage of fused silica

Abstract: Numerous experimental and theoretical contributions in the past have stressed the detrimental effect of fractures in the generation of surface laser damage sites in fused silica illuminated at 351 nm. However, two very important steps lack for the moment on the way towards a scientific understanding of the role of fractures. 1. a physical model must be developed to predict damage events starting from real defect sites 2. a reproducible measurement must be obtained and compared with calculations.Here we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In order to quantify this effect, we fit data from These values are only an indication of the 1w contribution. They have to be confirmed by numerical simulations [6]. According to Demos et al [7], the presence of a plasma is correlated with the growth phenomenon.…”
Section: Discussionmentioning
confidence: 76%
“…In order to quantify this effect, we fit data from These values are only an indication of the 1w contribution. They have to be confirmed by numerical simulations [6]. According to Demos et al [7], the presence of a plasma is correlated with the growth phenomenon.…”
Section: Discussionmentioning
confidence: 76%
“…Hence, a fracture surface involving quantum states in the forbidden band can play this role. 1 Several experiments suggest that surfaces are involved in laser energy absorption by dielectric materials, 5,6 more precisely a surface layer within the nanometer scale. 7 Accordingly, we introduce in our model such an absorbing layer ( Fig.…”
Section: Physical Modeling Of Laser-fracture Interactionmentioning
confidence: 99%
“…Various authors have shown that residual subsurface cracks existing in fused silica optics are likely to be precursors of laser damage [3][4][5][6]. Hence, efforts have been made by us and many others to measure and understand the impact of each manufacturing process step on the creation of subsurface damage (SSD) under the final fused silica surface [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%